Application of Fly Ash and Slag Generated by Incineration of Municipal Solid Waste in Concrete - Cong Zeng; Yan Lyu; Dehong Wang; Yanzhong Ju; Xiaoyu Shang; Luoke Li (Advances in Materials Science and Engineering)
As landfill space for the disposal of products of municipal solid waste incineration (MSWI) such as fly ash and slag becomes increasingly scarce, a reduction of disposed material is urgently required. The method of using incineration products in concrete production is explored in this paper through a feasibility study of utilizing fly ash and slag to replace cement and coarse aggregate in appropriate proportions. Results show that C30 concrete optimum replacement rates of fly ash and slag are 30% and 20%, which can meet the minimum strength requirement. The leaching concentrations of Cu, Zn, Pb, Cr, and Cd in MSWI concrete samples are determined to be less than the identification value of solid waste leaching toxicity. Based on scanning electron microscopy (SEM) and X-ray diffraction (XRD) analyses, MSWI fly ash has certain dispersion. The particle size of MSWI fly ash is determined to be close to that of the coal fly ash, and the surface morphology is irregular. The main components include SiO2, CaCO3, and Ca2SiO4, and they are similar to those present in the coal fly ash. The slag structure is loose as well as irregular, and its main component is SiO2. The SiO2 and Al2O3 in fly ash and slag participate in the hydration reaction of cement and can increase concrete strength. It is thus confirmed that fly ash and slag generated by waste incineration can be used to replace cement and coarse aggregate in appropriate proportions, and it is an effective method to solve the problem of scarcity of solid waste landfill space.